A curse so dark and lonely - Kemmerer, Brigid (Kemmerer, Brigid. Cursebreaker series, 2019)
Eighteen for the three hundred twenty-seventh time, Prince Rhen despairs of breaking the curse that turns him into a beast at the end of each day until feisty Harper enters his life.